Correlation between Chronic Pain with BDNF Levels, Histophatology of Hippocampus, and Spatial Memory in Wistar Rats - Budisulistyo, Trianggoro; Samekto, Widiastuti; Pudjonarko, Dwi; Suryawati, Herlina; Suryadi, Suryadi; Wahyuni, Maria (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Pain is defined as an unpleasant sensory and emotional experience associated with actural or potential tissue damage. Cognitive impairment can occur due to various processes in the brain, one of which resulted from chronic pain. Brain-derived neurotrophic factor (BDNF) is a neurotropin that plays a role in mediating disinhibition in the excitability of the motor cortex of the brain and inhibitory function in descending pain pathways. Chronic pain of periodontitis causes systemic inflammation that activates microglia resulting in degeneration of CA1 pyramidal neurons in the hippocampus and affects cognitive function, especially spatial memory. AIM: The objectives of this study were to determine the correlation between BDNF levels, spatial memory, and histopathology of hippocampus on periodontitis Wistar rats. METHODS: This observational prospective study was conducted between January and April 2022 at Laboratory Negeri Semarang University. Frontal inferior teeth ligation of Wistar rats was carried out to induce periodontitis for 4 weeks. Chronic pain was assessed using Rat Grimace Scale. Morris water maze (MWM) adaptation was applied for 4 weeks and then BDNF levels, spatial memory, and histopathology of hippocampus were investigated. T-test independent and spearman correlation test were used to data analysis. RESULTS: Among 12 rats, the mean of BDNF levels, spatial memory, and histopathology of hippocampus score were 7.57 ng/mL, 65.08 second, and 3, respectively. There were significant relationships between BDNF levels (p = 0.028), spatial memory (p = 0.001), and histopathology of hippocampus score (p = 0.017) on Wistar rats with chronic pain. Strong correlation (r = −0.721, r2 = 0.52, p = 0.004) between BDNF levels and spatial memory, and moderate correlation (r = −0.597, p = 0.02) between BDNF levels and histopathology of hippocampus score was obtained. There was no significant correlation between spatial memory and histopathology of hippocampus score. CONCLUSIONS: There were significant differences between BDNF levels, spatial memory, and histopathology of hippocampus on periodontitis Wistar rats.